1996
DOI: 10.1016/0300-2977(95)00069-0
|View full text |Cite
|
Sign up to set email alerts
|

Suggestive evidence for bromocriptine-induced pleurisy

Abstract: Pleurisy of initially unknown origin was found in a patient who was treated with bromocriptine for Parkinson's disease for 6 years. At presentation, bilateral pleural thickening existed that caused severe restriction of pulmonary function. There were an elevated erythrocyte sedimentation rate, polyclonal hypergammaglobulinaemia, increased levels of acute phase proteins and anaemia. After withdrawal of the bromocriptine the patient's complaints as well as the laboratory parameters markedly improved. Further los… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

1997
1997
2004
2004

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…In 1981, RINNE [2] reported that, out of 123 patients on long-term therapy with this drug, seven had developed pleuropulmonary reactions. Since then, to our knowledge, 30 cases of bromocriptine-induced adverse reactions in the lung and/or pleura have been reported in the literature [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Interestingly, ergot alkaloids other than bromocriptine can cause similar lesions in the chest [19].…”
mentioning
confidence: 99%
“…In 1981, RINNE [2] reported that, out of 123 patients on long-term therapy with this drug, seven had developed pleuropulmonary reactions. Since then, to our knowledge, 30 cases of bromocriptine-induced adverse reactions in the lung and/or pleura have been reported in the literature [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18]. Interestingly, ergot alkaloids other than bromocriptine can cause similar lesions in the chest [19].…”
mentioning
confidence: 99%